Anemia amongst patients with heart failure - a review - Dawid Burek; Aleksandra Paszkowska; Aleksandra Kujawa; Urszula Matuszewska; Aleksandra Nykowska; Katarzyna Beutler; Bartosz Bijata (Kazimierz Wielki University, 2024)
Introduction Anemia and iron deficiency are common comorbidities in population with heart failure. Their association with unfavorable prognostic outcomes and diminished quality of life underscores the imperative need for accurate diagnosis and efficacious treatment interventions. In recent years numerous treatment options have been explored in clinical trials, aimed at addressing the multifaced aspects of these concurrent conditions. Summary In patients with heart failure effective treatment of anemia and iron deficiency has demonstrated enhancements in quality of life and exercise capacity. Findings from IRONMAN clinical study have prompted revisions in the latest guidelines from the European Society of Cardiology. The imminent release of results from two ongoing trials holds the potential to reshape the therapeutic landscape for treating individuals with heart failure and iron deficiency. Nevertheless, there is no explicit evidence that studied interventions could improve morbidity or risk of hospitalizations.